Analysis of Vegetation Density and Surface Temperature in Buahbatu District, Bandung using Landsat 8 Oli/Tirs Satellite Images - Riki Purnama Putra; Rena Denya Agustina; Khansa Qurratu’Aini; Kanya Adwasyifa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2022)
Urban Heat Island is a phenomenon of increasing temperature that occurs in the city area compared to the surrounding area. Urban Heat Island is caused by reduced vegetation due to changes in rural land use to urban areas. This study was conducted to analysis the relation between vegetation density (NDVI) and surface temperature (LST) in Buahbatu District as an effort to control the impact of the Urban Heat Island phenomenon. This research was conducted by processing data from Landsat 8 OLI/TIRS satellite images in 2019-2020, namely from May to October 2019 and May to October 2020. Data collection was carried out through Google Earth Engine to retrieve geospatial data visualization (satellite imagery) and USGS to download Landsat 8 satellite imagery on Bands 4 and 5, then the data is processed using Arcmap, and Pearson correlation test is performed on SPSS. The results obtained are a correlation between vegetation density and surface temperature. In Buahbatu District, the correlation between vegetation density and surface temperature shows a value of (-.403*) in 2019 and (-.386*) in 2020. Both show a negative correlation, which means that if an area has high vegetation density, the surface temperature will decrease, and vice versa. In addition, Buahbatu District gets a good UHI with an NDVI above 0.25, and an LST below 30 but not less than 25.